PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN KOMUNIKASI TEMATIK MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA STKIP PGRI SUMBAR - ANGGRAINI S.Pd, VILLIA (Jurnal Pelangi : Research of Education and Development, 2012)
The cause of students’ low achievement in mathematic in teaching learningprocess is because the teaching method is not varied. Thus, this research is aimed tofind out: Are students’ communication mathematic using cooperative learning-STAD better than those who use conventional strategy. The population was studentsof 2009A and 2009E of STKIP PGRI west Sumatera in 2010/2011 academic yearwho was taken simple differential equations and the sample was purposive samplingtechnique. The instrument was post test which was analyzed using U Mann-Whitneytest. The data analysis shows that: Students who use cooperative learning-STADhave better competence on mathematic communication than those who useconventional strategy.